Sport Science Development And Sport Assistance Entrepreneurship Using The Easy Sport V1.0.1 Application Android Based On Village Volly Ball Club Sekarwangi, Cibadak District - Juli Candra; Truly Wangsalegawa; Octo Iskandara; Suharjudin; Desy Tya Maya Ningrum; M. Fadhli Nursal; Era Ramadona; Lukman Hakim (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Community Service Activities are carried out in Sekarwanggi Village for the Batu Asih Volley Ball Club in increasing the achievement abilities of volleyball athletes by using the Sport Science approach and increasing the economic capabilities of the people who are members of the Batu Asih Volley Ball club by using the Sport Entrepreneur approach. Community Service activities are carried out for five months, starting from May until September 2023. Initial activities in Community Service provide training to coaches and athletes in developing training programs by utilizing the use of Sport Science so that the Batu Asih Volly Ball club can create high-achieving athletes from from regional to national level. Then for the people who are members of the support for the development of the Batu Asih Volleyball Club, we also carry out activities to improve the economy by using Sport Entrepreneurship, so that sports activities can be packaged properly to improve the economy for the people in Sekarwanggi Village, Cibadak District. Then at the end of the PKM activity a volleyball match was held with the Batu Asih Cup II event, which was attended by 16 teams from the Cibadak sub-district which was held for four days.